EMPLOYEES PERCEPTION OF WORKPLACE MONITORING AND SURVEILLANCE - Jahagirdar, Renu; Bankar, Swati (PEOPLE: International Journal of Social Sciences, 2020)
Employee monitoring has gained importance from different interest groups – Commercial organisations, employee interest groups, privacy advocates, professional ethicists and lawyers. It is a practice of organizational management. It is about surveying the employee’s activity through various surveillance methods. The objectives of employee monitoring can be performance tracking, avoiding legal liability, protection of trade secrets and also to focus security concerns if any. The policy of monitoring and surveillance is likely to have a negative effect on employee satisfaction and employee privacy though, it is essential to identify and prevent unacceptable behaviour of employees if any. Employee monitoring trend has evolved gradually as a result of technological innovation. This research paper analyses the impact of employee monitoring practices in organisations. The study proposes organizational theories, privacy theories, control theories and resource theories so as to address the employee privacy issues. These multiple theories indicate multiple dimensions focusing on the proactive approach or a backup plan mediating between organisational policy and behaviour of employees. Result of the study indicates that Employee Commitment level dependents on employee’s perception about their privacy at workplace. This perception is influenced by management practices such as organisational policy and prevention of misuse.